Improvement of bus roof section - Ahmad Farhan Hakim, Azmi (2008)
Modern transit buses are an integral part of the national transportation system. According to BERNAMA, in 2007 there were about 10.8 percent increasing of people who used bus as their daily transportation in Malaysia. Although buses are one of the safest means of transportation, occupant injuries and fatalities in bus accident do occur. Rollover strength has become an important issue for bus and coach manufacturers. So, this project is basically about to investigate the bus structure used in Malaysia. As we all know, there is little amount of literature found related to bus design and safety aspect. With this project, it is hoped to increase awareness to bus safety aspect especially in bus roof section and in improving the bus roof structure. This report discusses the development of a finite element (FE) analysis for the improvement of bus roof section. The FE model was validated according to the reference journal sources and some standard guideline from European regulation “ECE-R66” were applied in this project. For that, a few current bus structures were use as benchmark and compared in this project. This bus design will then be improved around the roof section to make sure the structure can withstand more force or impact especially during accident thus can minimize the risk of bus occupants from getting severe injuries.